2005
DOI: 10.1007/s10038-005-0331-z
|View full text |Cite
|
Sign up to set email alerts
|

Association study of semaphorin 7a (sema7a) polymorphisms with bone mineral density and fracture risk in postmenopausal Korean women

Abstract: Bone mineral density (BMD), the major factor determining bone strength, is closely related to osteoporotic fracture risk and is determined largely by multiple genetic factors. Semaphorin 7a (SEMA7A), a recently described member of the semaphorin family, has been shown to play a critical role in the activation of monocyte/macrophages that share progenitors with bone-resorbing osteoclasts and thus might contribute to osteoclast development. In the present study, we directly sequenced the SEMA7A gene in 24 Korean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 23 publications
3
47
0
Order By: Relevance
“…In an in vitro model of periodontal ligament remodeling in tension, where bone formation is stimulated and osteoclastic resorption is inhibited, Sema7A was repressed, consistent with a resorptive role for this semaphorin [71]. Furthermore, human Sema7A single nucleotide polymorphisms are associated with decreased bone mass and increased fracture risk [72]. Thus, Runx2-mediated increase in Sema7A in mesenchymal progenitors and osteoblasts likely contributes to their increased ability to induce osteoclastogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…In an in vitro model of periodontal ligament remodeling in tension, where bone formation is stimulated and osteoclastic resorption is inhibited, Sema7A was repressed, consistent with a resorptive role for this semaphorin [71]. Furthermore, human Sema7A single nucleotide polymorphisms are associated with decreased bone mass and increased fracture risk [72]. Thus, Runx2-mediated increase in Sema7A in mesenchymal progenitors and osteoblasts likely contributes to their increased ability to induce osteoclastogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated for the first time the possible involvement of Sema-7A in bone cell differentiation [Delorme et al, 2005]. Recently, it was also shown that polymorphisms of the Sema-7A gene were associated with the bone mineral density of the lumbar spine and the femoral neck [Koh et al, 2006].…”
Section: Introductionmentioning
confidence: 89%
“…However, recent studies have shown that many of the semaphorins and their receptors are also expressed by osteoblasts and osteoclasts. Furthermore, they were found to play an important role in the development and remodeling of bone through the regulation of osteoblast or osteoclast differentiation [Harper et al, 2001;Delorme et al, 2005;Koh et al, 2006;Tamagnone and Giordano, 2006]. As is the case for the other secreted chemorepellents for the guidance of neuronal axons and neurons, slits have similar molecular structure and func- Results were standardized using GAPDH as a housekeeping gene and then expressed as relative mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…SEMA7A polymorphisms are associated with abnormal bone mineral density in Korean women (72). During acute lung injury, TGFB1 can increase endothelial and epithelial permeability (73)(74)(75), and the inhibition of TGFB1 can diminish lung injury (66,(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%